HATE CRIMES COMMITTED IN KOSOVO AND METOHIA (Heritage, 2025)
Hate crimes have a strong motivation, which is based on hatred towards members of certain national and religious groups, and hatred can occur in relation to national and ethnic origin, language, script, race, skin color, religious affiliation, gender, sexual orientation, disability and the like.A hate crime is a criminal act that is committed only against a person who is different from the perpetrator. The Criminal Code of the Republic of Serbia recognizes hate crimes and defines hatred as an aggravating circumstance in those situations when a criminal act is committed due to hatred towards a person because they belong to a certain racial or religious group. Hatred arises due to difference and is not directed only towards an individual who is a specific victim of a criminal act, but towards all members of a certain nation, religious group, persons who speak a certain language or have some other significant characteristics that distinguish them from the majority.Members of the Serbian people in Kosovo and Metohija were victims of hate-motivated crimes by the majority Albanian people. The paper will highlight the crimes committed against Serbs solely because of their national and religious differences from Albanians.
Keywords: hatred, motive, crime, murders, pogrom.